Influences of semantic and syntactic incongruence on readiness potential in turn-end anticipation - Wesselmeier, Hendrik; Jansen, Stefanie; Müller, Horst M. (Frontiers in Human Neuroscience, 2014)
Knowing when it is convenient to take a turn in a conversation is an important task for dialog partners. As it appears that this decision is made before the transition point has been reached, it seems to involve anticipation. There are a variety of studies in the literature that provide possible explanations for turn-end anticipation. This study particularly focuses on how turn-end anticipation relies on syntactic and/or semantic information during utterance processing, as tested with syntactically and semantically violated sentences. With a combination reaction time and EEG experiment, we used the onset latencies of the readiness potential (RP) to uncover possible differences in response preparation. Although the mean anticipation timing accuracy (ATA) values of the behavioral test were all within a similar time range (control sentences: 108 ms, syntactically violated sentences: 93 ms and semantically violated sentences: 116 ms), we found evidence that response preparation is indeed different for syntactically and semantically violated sentences in comparison with control sentences. Our preconscious EEG data, in the form of RP results, indicated a response preparation onset to sentence end interval of 1452 ms in normal sentences, 937 ms in sentences with syntactic violations and 944 ms in sentences with semantic violations. Compared with control sentences, these intervals resulted in a significant RP interruption for both sentence types and indicate an interruption of preconscious response preparation. However, the behavioral response to sentence types occurred at comparable time points.